Sensory profiles and oxidative stability of linseed oil microencapsulated with pea, soy, and whey proteins in high-fat food models - Hakanen, Sari A.; Damerau, Annelie; Ogrodowska, Dorota; Seubert, Annalisa; Brandt, Waldemar; Laaksonen, Oskar; Tanska, Malgorzata; Linderborg, Kaisa M. (ELSEVIER, 2025)
To hinder oxidation and mask flavor, linseed oil was encapsulated using maltodextrin with pea, soy, or whey protein, and incorporated in dark chocolate and shortbread cookie models. While the spray dried emulsions with whey protein and maltodextrin were most stable, this behaviour did not translate to food models. In volatiles, the fortification with pea protein capsules had closer resemblance to the control than other spray-dried samples. Storage time increased the volatiles of particularly soy and whey samples. In flavor, the pea sample, and in appearance and texture, the soy sample resembled closest the control chocolate. Addition of the spray dried emulsion increased the darkness, rancidity, roasted flavor, and hardness of the cookies. While the pea protein emerged as an intriguing choice for shell material in spray-drying of linseed oil, also fortification with nonencapsulated linseed oil resulted in favorable outcomes based on sensory perception and volatile profiles of the food models.